Righteous prey [large type] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel, 2022)
"'We're going to murder people who need to be murdered.' So begins a press release from a mysterious group known only as "The Five," shortly after a vicious predator is murdered in San Francisco. The Five is believed to be made up of vigilante killers who are very bored and very rich. They target the worst of society and then use their unlimited resources to offset the damage by donating untraceable Bitcoin to charities and victims via the dark net. After a woman is murdered in the Twin Cities, Virgil Flowers and Lucas Davenport are sent in to investigate. If anyone can destroy this group, it will be the dynamic team of Davenport and Flowers"--